2016
DOI: 10.1002/acn3.331
|View full text |Cite
|
Sign up to set email alerts
|

Terminal complement activation is increased and associated with disease severity in CIDP

Abstract: Chronic inflammatory demyelinating polyneuropathy (CIDP) is the most common chronic autoimmune neuropathy. While both cell‐mediated and humoral mechanisms contribute to its pathogenesis, the rapid clinical response to plasmapheresis implicates a circulating factor responsible for peripheral nerve injury. We report that treatment‐naïve patients with CIDP show increased serum and CSF levels of the anaphylatoxin C5a and the soluble terminal complement complex (sTCC). Systemic terminal complement activation correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Supporting the hypothesis that complement activation can be a potential pathogenic mechanism for this disease, complement component C3d deposition has been detected on the outer surface of PNS Schwann cells in biopsies from patients with CIDP [60,64,65]. Moreover, clinical studies demonstrated that CIDP patients have increased serum and cerebrospinal fluid levels of C5a [66], which is the result of the proinflammatory function of C3d aimed at recruiting myeloid cells, such as macrophages, to inflammation sites through complement receptors and inducing tissue injury through formation of the MAC. These findings suggest that systemic and local terminal complement activation is a characteristic feature of inflammatory demyelinating polyneuropathies and support a role of complement activation in the pathogenesis of CIDP.…”
Section: Chronic Inflammatory Demyelinating Polyradiculoneuropathymentioning
confidence: 76%
“…Supporting the hypothesis that complement activation can be a potential pathogenic mechanism for this disease, complement component C3d deposition has been detected on the outer surface of PNS Schwann cells in biopsies from patients with CIDP [60,64,65]. Moreover, clinical studies demonstrated that CIDP patients have increased serum and cerebrospinal fluid levels of C5a [66], which is the result of the proinflammatory function of C3d aimed at recruiting myeloid cells, such as macrophages, to inflammation sites through complement receptors and inducing tissue injury through formation of the MAC. These findings suggest that systemic and local terminal complement activation is a characteristic feature of inflammatory demyelinating polyneuropathies and support a role of complement activation in the pathogenesis of CIDP.…”
Section: Chronic Inflammatory Demyelinating Polyradiculoneuropathymentioning
confidence: 76%
“…In CIDP, complement and IgG are deposited on myelinated fibres 47 and serum levels of terminal complement activation components increase with disease severity 48 . However, complement-fixing antibodies to compact myelin, which would explain the active demyelination and conduction block, have not been identified in CIDP.…”
Section: Inappropriate Complement Activationmentioning
confidence: 99%
“…To support the efficacy of eculizumab in patients with AIDP, a recent study of sural nerve biopsy specimens obtained from patients with AIDP demonstrated the deposition of complements [40]. The activation of complements has also been reported in some patients with CIDP [28,[74][75][76]. As described earlier, humoral immunity may be more predominant in typical CIDP than in atypical CIDP, and complement inhibition might be another therapeutic option in a subpopulation of patients with CIDP.…”
Section: Insights Into Classification and Therapeutic Strategiesmentioning
confidence: 91%